An Analysis Reduplication of Sabu Language in Eikare Village Sabu Liae District Sabu Raijua Regency - Rohi, Libertina; Anabokay, Yanrini M.; Dewi, Ni Putu Juliani Lestari (Journal of English Culture, Language, Literature and Education, 2025)
This research is An Analysis Reduplication of Sabu Language In Eikare Village Sabu Liae District Sabu Raijua Regency. The purpose of this research are (1) to find out the forms of reduplication in the Liae dialect of the Sabu language and (2) to find out the functions of reduplication in the Liae dialect of the Sabu Language. The research method that the researcher used is qualitative descriptive. The researcher takes two native speakers as informants in the Liae dialect of the Sabu Language. The instrument used in this research is thirty sentences in Indonesian, then translated into the Sabu Language. The researcher will use three data collection techniques: transcribing, identifying, and analyzing. Reduplication in the Sabu language is often used to give intensification or quantity to these words. For example, in the Sabu language, the noun is used to express the number of objects, such as manu-chicken into manu-manu-chickens. In addition, expressing repeated actions, such as bejhi-sleep becoming bejhi-bejhi, means to lie down. It should be noted that reduplication in the Sabu language is not just a repetition of words without phonological and morphological changes. Each type of reduplication has specific rules and functions, so it is necessary to analyze to understand the concept. The results of this research are expected to positively contribute to the field of linguistics, especially in improving the understanding of regional languages, developing literacy, and supporting local cultural preservation efforts by promoting the importance of the Sabu language in the cultural context of the Sabu community